Little Classics Easy Pieces for the Piano: Book I - CLEMENTI, Muzio (G.Schirmer, 1909)
Buku ini terdiri dari 29 lagu, yaitu arie, preludio, siciliano, allegreno, andame, six easy variations on an original theme, rondo, la matinee, chorus, largo, lascia minuet, serena, la bella capricciosa, la ceneremola, barcarola, skating, confidence, consolation, rondo, minuet,turkish march, moment musical, the merry farmer returningfrom work, wildr reiter, butterfly, glipsy dance, valse, invitation to the dance